Solve : -7 + 6 ( p - 3 ) = 17
Answers
Answered by
0
Answer:
6
Step-by-step explanation:
-7+6p-18=17
6p-25=17
6p=17+25
6p= 42
p=42/7
p= 6
MARK AS BRAINLIEST PLZZZZ>>>>>/......
Answered by
0
Hope it helps you
IF IT HELPS YOU THEH MARK ME THE BRAINLIEST ONE
-7+6(p-3)=17
-7+6p-18=17
-7-18+6p=17
-25+6p=17
6p=17+25
6p=42p
p=42/6
p=7/1=7
Sorry the picture is not uploading
Attachments:
![](https://hi-static.z-dn.net/files/d7c/c297dc967451ecede6110af7e2d8206c.jpg)
Similar questions
Math,
5 months ago
Math,
5 months ago
Math,
11 months ago
Social Sciences,
11 months ago
Math,
1 year ago